ANALISIS PUISI â€œSURAT CINTAâ€ DAN â€œMALAIKAT DI GEREJA ST. JOSEFâ€ KARYA W. S. RENDRA: PENDEKATAN SEMIOTIKA RIFFATERRE - Yohanes Vianey Ona; Widowati Widowati (CARAKA, 2017)
The purpose of this research is to describe and explain the following things: (1) indirect expressions; (2) heuristics and hermeneutic analysis; (3) matrix, models, and variants; (4) hipograms variable; which are contained in "Surat Cinta" and "Malaikat di Gereja St. Josef", poems written by W. S. Rendra. This is a qualitative research. The data which are used in this research are linguistic aesthetical units, consist of words, phrases, lines, and stanzas in the poems. The data resources are poems written by W. S. Rendra, entitled "Surat Cinta" and "Malaikat di Gereja St. Josef". The research instrument is the researcher himself who provides insight and experience about semiotic theory dealing with the analysis of the poems, especially Riffaterre semiotic theory. The data collecting method which is used in this research is a literature exploration which is conducted by reading and noting techniques. Qualitative is the method which is used to analyze the data, while qualitative descriptive is the conducted technique in term of analyzing the process. The process taken has brought the researcher to the following conclusions. 1) Indirect expressions includes the changing of wordsâ€™ meaning, for example, /surat cinta/ caused by ambiguity, /bagai berjuta-juta jarum alit/ which is a linguistic term called kias simile or comparison, /tiada lebih buruk dan tiada lebih baik /, / orang yang bermula dari kata kata yang bermula dari kehidupan pikir dan rasa / which are linguistic kias epik simile or parable of the epic. /Engkau adalah putri duyung / is a personification stylistic. The whole part of "Surat cinta" is in allegory stylistic. Putri duyung is a kias sinekdoki. /Kutulis surat ini kala hujan gerimis bagai bunyi tambur/ shows the use of fantasy or imagination overview. The deviations meaning in "surat cinta" are caused by ambiguity, for instance, /surat cinta/, the new meaning of sentences caused by rhyme: an end rhyme, for example /Putri duyung dengan suara merdu lembut bagai angin laut/, straight rhyme, for example /Angin mendesah selalu mendesah/, while /kala langit menangis/ is an example assonance rhyme and /menangis minta mainan/ is an alliteration rhyme. The deviations meaning also can be caused by enjambments, for example, /Dan angin mendesah mengeluh dan mendesah/, and homologs, for example, /orang yang bermula dari kata kata yang bermula dariâ€¦/ 2) Heuristics and hermeneutic analysis, 3) Matrix, models, and variants. For example, the matrix of "Malaikat di Gereja St. Josef" describes something that God has planned to humankind which appears with the angel in St. Josef church. The models in that poem are "St. Josef" and "Angel", and those models are described by the following variant: /Malaikat di Gereja St. Josef/. 4) The hipograms of "Surat cinta" are: (a) expansion: â€œSajak Putihâ€ (1944) and â€œDerai-Derai Cemaraâ€ (1949) by Chairil Anwar. (b) modification: â€œSajak Putihâ€ (1944) by Chairil Anwar. (c) actual: â€œLagu Gadis Italiâ€ (1920s) by Sitor Situmorang and â€œDalam Gelombangâ€ (1920s) by St. Takdir Alysahbana, whereas the hipograms of "Malaikat di Gereja St. Josef" are: (a) Ekserp: â€œTurun Kembaliâ€ (1937) by Amir Hamzah. (b) Modification: â€œPanggilan Pagi Mingguâ€ by Y. E. Tatengkeng. (c) Actual: poem â€œBarangkaliâ€ by Amir Hamzah.